Evaluation of Efficiency Investment Activity of Gas Distribution Companies: Methodological Aspects - Король, С. В. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The main techniques of analysis and evaluation of economic efficiency of investment and innovative activity of the enterprises have been analysed and characterised. Special attention was dedicated to the selection of the most effective methods of implementing such assessment on the example of gas distribution enterprises, the main indicators of assessment of innovation activity of enterprise were offered.